Pembaharuan Hukum Pidana terhadap Tindak Penyalahgunaan Kekuasaan (Abuse of Power) dalam Sistem Hukum Indonesia - Kadek Purbhawadi; I Nengah Suastika; Dewa Gede Herman Yudiawan (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study discusses the reform of criminal law regarding acts of abuse of power within the Indonesian legal system. Abuse of power committed by public officials constitutes a serious violation of the rule of law and the principle of equality before the law because it can harm society and weaken public trust in the government. The old Criminal Code inherited from the colonial era was considered incapable of providing an optimal deterrent effect against perpetrators of abuse of authority. Therefore, the enactment of Law Number 1 of 2023 concerning the New Criminal Code became an important step in the reform of criminal law in Indonesia. This study aims to analyze criminal law reform policies in overcoming abuse of power and the effectiveness of their implementation in law enforcement. The results show that the new Criminal Code expands regulations regarding abuse of authority with stricter criminal sanctions and additional penalties in the form of revocation of office rights. However, its implementation still faces challenges such as political intervention, low integrity of law enforcement officials, and the potential overlap with the Corruption Eradication Law. Therefore, the success of criminal law reform requires the support of legal substance, legal structure, and legal culture that work in harmony.